Covid-19: Face Mask Protection in the Pediatric Setting - XINIAS, Ioannis (Maedica (Bucur), 2021)
We report our experience regarding a pediatric patient-case who had a covid-19 infection, which was initially considered a common viral infection and was managed accordingly for the first 36 hours while being hospitalized. Wearing a simple surgical face mask was the only protective measure which our personnel has adopted. All staff members were tested for covid-19 infection with swab specimens from the nasopharynx and pharynx and were found to be negative in 7-10 days after coming into contact with the patient. Thirty-one days after contact with the covid-19 patient, no one of the staff members had respiratory symptoms, and therefore, they all returned to work. This case shows the importance of face-mask wearing to prevent the transmission various of respiratory infections, including that caused by the novel SARS-CoV-2 microorganism.